TRANSITION PARADIGM TOWARDS AN ENVIRONMENTAL RATIONALITY IN BRAZIL - Girardon dos Santos, Denise Tatiane; Benedetti Rodrigues, Domingos (Revista Digital Constituição e Garantia de Direitos, 2024)
The environmental crisis demands measures to deal with it, based on intergenerational and ecocentric paradigms. Based on the Convention on Biological Diversity, as an international prerequisite for preserving environmental balance, and the Constitution of the Federative Republic of Brazil, the aim is to point out the legal bases for the transition to an environmental rationality in Brazil. The state is obliged to take on the role of the rule of law for the environment in the way it acts, before international and domestic legislation, environmental education and sustainable development, in their legal, environmental, political, cultural and social aspects. Methodologically, the research is qualitative, descriptive and longitudinal. It concludes that the rule of environmental law is an alternative for building the transition to environmental rationality, by promoting environmental education and sustainable development.